Continuous positive airway pressure care for pediatric obstructive sleep apnea: A long‐term quality improvement initiative. Issue 11 (22nd July 2022) - Xanthopoulos, Melissa S.; Williamson, Ariel A.; Burlingame, Caroline C.; Afolabi‐Brown, Olufunke; Tapia, Ignacio E.; Cielo, Christopher; Moore, Melisa; Beck, Suzanne E.
Abstract: Successful treatment of pediatric obstructive sleep apnea syndrome (OSAS) with continuous positive airway pressure (CPAP) is challenging due to behavioral, technical, medical, and systems factors. We undertook a quality improvement (QI) initiative involving physicians, nurses, psychologists, and respiratory therapists to improve CPAP outpatient care and processes. We aimed to: (1) increase the proportion of patients with a follow‐up visit within 4 months of initiation of CPAP, (2) reduce the median time to first follow‐up visit to under 4 months, and (3) increase the proportion of patients obtaining a post‐initiation polysomnogram within 1 year to >50%. We also explored healthcare utilization (HCU) in a subsample of patients. Interventions focused on developing a tracking system and standardizing interdisciplinary clinical care. The proportion of patients returning to clinic within 4 months improved from 38.2% to 65.5% and median time to first follow‐up visit improved from 133 to 56 days. The percentage of patients who returned for a post‐initiation polysomnogram within 1 year was 71.1%. Subsample analyses showed significant reductions in the length of stay for emergency department visits from pre‐CPAP initiation (Mdn = 3.00 h; interquartile range [IQR] = 7.00) to post‐initiation (Mdn = 2.00 h, IQR = 5.00). The length of hospitalizations was also significantly shorter from pre (Mdn = 48.00 h, IQR = 243.00) to post‐CPAP initiation (Mdn = 0.00 h, IQR = 73.00). A standardized, tracked approach to interdisciplinary outpatient CPAP care can improve follow‐up care and potentially HCU.